Fertilization changes soil microbiome functioning, especially phagotrophic protists. (September 2020) - Zhao, Zhi-Bo; He, Ji-Zheng; Quan, Zhi; Wu, Chuan-Fa; Sheng, Rong; Zhang, Li-Mei; Geisen, Stefan
Abstract: The soil microbiome determines crop production and drives nutrient cycling, functions that are altered by fertilization. Yet, we have only begun to understand the effects of fertilization on taxonomic changes on soil microorganisms, while impacts on functional groups across the microbiome and therefore potential soil functioning have never been assessed. Here, using a range of methods including high-throughput sequencing, we identified 77 functional parameters of the main microbiome groups including bacteria, fungi, and protists in three common agricultural soil types in China (black, fluvo-aquic, and red soil), which were fertilized in the same way over two years. We show that fertilization most strongly and generally throughout soil types reduced the relative abundance of the main microbial predators, phagotrophic protists, by 31%. Ten functional groups within the microbiome showed soil type-specific responses to fertilization. For example, ammonia-oxidizing bacteria, and predatory/exoparasitic bacteria were reduced by fertilization in the acidic black and the red soils, while, no other microbial functional group than phagotrophic protists was suppressed by fertilization in the alkaline fluvo-aquic soil. The significant reductions in microbial functional groups especially in acidic soils could be explained by nitrogen enrichment, increased soil acidification and potential biotic links between the functional groups within the microbiome. Together, we show that the fertilization-induced abiotic changes alter microbial functions that depend on the soil and environmental conditions. Particularly the most profound changes on the group of microbial predators might subsequently affect other soil functions performed by bacteria and fungi. Highlights: Microbiome functioning was affected by fertilization in a soil-specific manner. Fertilization reduced AOB and predatory/exoparasitic bacteria in acidic soils. Only phagotrophic protists were suppressed by fertilization across all soil types. Fertilizer-induced changes on protists likely alter entire microbiome functioning.